Identification of estrogen-regulated genes by microarray analysis of the uterus of immature rats exposed to endocrine disrupting chemicals - Leung Peter CK; Choi Kyung-Chul; Park Se-Hyung; Hong Eui-Ju; Jeung Eui-Bae (BMC, 2006)
Abstract Environmental estrogenic compounds which bind to the estrogen receptor (ER) can block or alter endogenous functions of estrogen in reproductive and developmental stages. A microarray technology is a very valuable method for the prediction of hormone-responsive activities in various gene expressions. Thus, we investigated the altered gene expression by estrogen and endocrine disruptors (EDs) using microarray technology in the uterus of immature rats. In this study, the expression levels of only 555 genes (7.42%) among the 7636 genes spotted on microarray chips were enhanced by more than two-fold following treatment with estradiol (E2), suggesting that direct or rapid response to E2 is widespread at the mRNA levels in these genes. In addition, elevated expression levels of the genes (over 2-fold) were observed by diethylstilbestrol (DES; 9.01%), octyl-phenol (OP; 8.81%), nonyl-phenol (NP; 9.51%), bisphenol-A (BPA; 8.26%) or genistein (9.97%) in the uterus of immature rats. The expression levels of representative genes, i.e., calbindin-D9k (CaBP-9k; vitamin D-dependent calcium-binding protein), oxytocin, adipocyte complement related protein (MW 30 kDa), lactate dehydrogenase A and calcium binding protein A6 (S100a6; calcyclin), were confirmed in these tissues by real-time PCR. In addition, the mRNA levels of these genes by real-time PCR were increased at follicular phase when E2 level was elevated during estrous cycle of adult female rats. In conclusion, these results indicate distinct altered expression of responsive genes following exposure to E2 and estrogenic compounds, and implicate distinct effects of endogenous E2 and environmental endocrine disrupting chemicals in the uterus of immature rats.